2013
DOI: 10.1016/j.jaci.2013.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced production of IL-17A in patients with severe asthma is inhibited by 1α,25-dihydroxyvitamin D3 in a glucocorticoid-independent fashion

Abstract: PBMC cultures from asthma patients synthesised high levels of IL-17A compared to non-asthmatic controls, most significantly in steroid refractory patients. Glucocorticoids could enhance IL-17A, but 1,25(OH)2D3 inhibited this response in a glucocorticoid-independent manner. Nanzer et al 3 AbstractBackground: Th17 cells are proposed to play a role in the pathology of asthma, including steroid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
148
3
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(167 citation statements)
references
References 49 publications
9
148
3
7
Order By: Relevance
“…Inactivation of protease activity led to reduction in allergic parameters. These results demonstrate that proteolytic activity of Per a 10 potentiates its allergenicity.There was an increase in levels of IL-17A in the sputum of severe asthmatics [23] and may act as a marker and risk factor for severe asthma [24]. Previously, it was shown that GC frass induces IL-17A secretion in a PAR-2-dependent manner.…”
mentioning
confidence: 89%
“…Inactivation of protease activity led to reduction in allergic parameters. These results demonstrate that proteolytic activity of Per a 10 potentiates its allergenicity.There was an increase in levels of IL-17A in the sputum of severe asthmatics [23] and may act as a marker and risk factor for severe asthma [24]. Previously, it was shown that GC frass induces IL-17A secretion in a PAR-2-dependent manner.…”
mentioning
confidence: 89%
“…From a mechanistic point-of-view, it is interesting that ZHAO et al [45] were able to demonstrate a positive correlation between IL-17A and IL-23 protein in the group of patients with allergic asthma, since this is compatible with IL-23 constituting a trigger of IL-17A production in circulating Th17 cells. In a recently published study on blood Th cells from healthy control subjects and patients with moderateto-severe asthma who had been without treatment with glucocorticoids for 4 weeks, NANZER et al [46] found that the intracellular immunoreactivity for IL-17A and IL-22 was enhanced in patients with ''steroidrefractory'' but not ''steroid-sensitive'' clinical disease. The blood Th cells co-expressing IL-17A and IL-22 were enhanced in all patients with asthma, as was the corresponding release of extracellular protein in vitro.…”
Section: Systemic Involvementmentioning
confidence: 99%
“…However, in the absence of such a premorbid abnormality in steroid signaling there is no unifying explanation of the SR phenotype. Candidate mechanisms include overexpression of the inhibitory β-isoform of the GR (GR-β) (1,5), but there is also increasing evidence to suggest that specific variations in the adaptive immune response to glucocorticoid therapy play a key role (6)(7)(8).…”
mentioning
confidence: 99%